2016
DOI: 10.5433/1679-0359.2016v37n2p807
|View full text |Cite
|
Sign up to set email alerts
|

Blood parameters of sheep with high infection of Haemonchus contortus and treated with “mushroom of the sun” (Agaricus blazei)

Abstract: Parâmetros sanguíneos de ovinos com alta infecção porHaemonchus contortus e tratados com "cogumelo do sol" (Agaricus blazei) AbstractBlood and parasitological parameters of sheep experimentally infected with Haemonchus contortus and treated with "mushroom of the sun" (Agaricus blazei) were assessed. Lambs infected with the nematode were divided into three groups: treated with basidiocarp powder from the fungus, wormed with trichlorfon, and a control group that did not receive anthelmintic. Split-plot design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…However, ABE alone did not affect protein parameters. These finding may be partially consistent with those of Bastos et al (2016) who found that animals (sheep model) treated with trichlorfon (10 mg/g bw) and Agaricus blazei (11.14 g/kg bw) showed progressive recovery of albumin, globulins, and total protein concentrations, returning to the baseline level after 21 days, unlike that in the control group received trichlorfon only. However, our findings may be inconsistent with those of Junior et al (2016) who found that Agaricus blazei extract (2.5 g/kg bw) given for 21 days to albino mice has no significant differences in the levels of serum concentrations of total protein, albumin, and inhibited the increase of gamma-globulin with Ehrlich tumor that is associated with marked decrease in albumin (thus, is considered to be a protein of the negative acute phase) and other protein fractions.…”
Section: Liver Function Parameterssupporting
confidence: 91%
“…However, ABE alone did not affect protein parameters. These finding may be partially consistent with those of Bastos et al (2016) who found that animals (sheep model) treated with trichlorfon (10 mg/g bw) and Agaricus blazei (11.14 g/kg bw) showed progressive recovery of albumin, globulins, and total protein concentrations, returning to the baseline level after 21 days, unlike that in the control group received trichlorfon only. However, our findings may be inconsistent with those of Junior et al (2016) who found that Agaricus blazei extract (2.5 g/kg bw) given for 21 days to albino mice has no significant differences in the levels of serum concentrations of total protein, albumin, and inhibited the increase of gamma-globulin with Ehrlich tumor that is associated with marked decrease in albumin (thus, is considered to be a protein of the negative acute phase) and other protein fractions.…”
Section: Liver Function Parameterssupporting
confidence: 91%
“…Observam-se ainda interferências na solubilidade de macro e microelementos e diminuição da digestibilidade das proteínas adquiridas na alimentação e provenientes das perdas de sangue, muco e células epiteliais esfoliadas (9). As perdas de proteínas sanguíneas provocam um aumento do fluxo de nitrogênio para o duodeno, grande parte desse nitrogênio sanguíneo é convertida pelos parasitas em NH 3 , resultando em maior síntese de uréia devido ao metabolismo hepático e aumentando o requerimento de proteínas pelo hospedeiro (10). A presença de Haemonchus contortus e outros helmintos gastrointestinais no abomaso pode mudar a acidez local necessária para a operação adequada de enzimas catalíticas que têm um pH ótimo extremamente baixo.…”
Section: Introductionunclassified